Preparation and Characterization of Glass-Ceramics Synthesized from Soda Lime Glass and Wastewater Sludge - Zaibon, Syaharudin (2011)
This project reports the utilization and vitrification of wastewater sludge (WS) and soda lime silica (SLS) glass via converting them into glass-ceramic materials. The vitrification method has been used and also exploited as a solution for the disposal of WS and SLS glass and to minimize any environmental hazards. The glass ceramics were prepared from a mixture of wastewater sludge and SLS glasses and melted at 1375 °C for 3 hours and quenched by pouring it into water to obtain a coarse frit. The frit glass was then crushed and sieved to 106μm and pressed into a pellet. The sintering process was performed at various temperatures between 700-1000 °C for 2 hours at 50 ºC intervals. The combination of WS and SLS provided a suitable chemical composition for the production of glass-ceramic. The resulting samples were then characterized using energy dispersive X-ray fluorescence spectrometer (EDXFS), differential thermal analysis (DTA), X-ray diffraction (XRD), scanning electron microscopy (SEM) and laser flash apparatus (LFA). In this work, a thermal diffusivity measuring apparatus was used for measurement of thermal diffusivity (α) of glasses and glass-ceramics. The measurements of α were carried out at room temperature up to 300 °C with the intervals of 50 °C. Experimental results showed that α value for samples A (25%WS 75%SLS) are in the range of 0.386 - 0.767 mm2s-1, samples B (20%WS 80%SLS) are in the range 0.322 - 0.726 mm2s-1, samples C (15%WS 85%SLS) are in the range 0.3 - 0.66 mm2s-1, samples D (10%WS 90%SLS) are in the range 0.283 - 0.623 mm2s-1, and for samples E (5%WS 95%SLS) are in the range 0.24 - 0.615 mm2s-1. The changes of the nature of the crystallinity of the samples, heat treatment temperature and changes of the density value have been suggested to be responsible for the variation in the thermal diffusivity behavior. DTA study indicated that there were only inflection points of the endothermic peaks in the DTA curves of the glass samples. XRD analysis showed the amorphous state of the glass samples and also the presence of the diopside sodian, augite, cristobalite low and calcium silicate phases in the heat-treated samples. SEM investigations revealed that small amount of crystallites occurred in the microstructure of the heat treated samples such as flower shape, hemispherical shape, leaf shape, flaky shape and also residual glassy phase in contrast to the amorphous structure of the samples. It is recommended that future researches can be carried out to develop a good quality of glass-ceramic and would make them attractive to industrial application such as study in hardness, bend strength, erosive wear resistance, fracture strength and toughness.